2022
DOI: 10.1038/s41380-021-01421-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain rewiring and altered cortical stability in ulcerative colitis

Abstract: Despite recent advances, there is still a major need to better understand the interactions between brain function and chronic gut inflammation and its clinical implications. Alterations in executive function have previously been identified in several chronic inflammatory conditions, including inflammatory bowel diseases. Inflammation-associated brain alterations can be captured by connectome analysis. Here, we used the resting-state fMRI data from 222 participants comprising three groups (ulcerative colitis (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Meanwhile, the researchers also found that the hippocampal nerve activity is increased with IBD in the active phase compared with those in remission ( 168 ). Additionally, a dynamic brain functional connectome analysis using fMRI has revealed medial prefrontal cortex dysfunction, which is involved in the deterioration of depression and anxiety in patients with UC ( 169 ). Those studies provide a promising perspective and convincing neuroimaging evidence of potential neuromechanisms of UC.…”
Section: Application Of Neuroimaging Studies In Evaluating the Possib...mentioning
confidence: 99%
“…Meanwhile, the researchers also found that the hippocampal nerve activity is increased with IBD in the active phase compared with those in remission ( 168 ). Additionally, a dynamic brain functional connectome analysis using fMRI has revealed medial prefrontal cortex dysfunction, which is involved in the deterioration of depression and anxiety in patients with UC ( 169 ). Those studies provide a promising perspective and convincing neuroimaging evidence of potential neuromechanisms of UC.…”
Section: Application Of Neuroimaging Studies In Evaluating the Possib...mentioning
confidence: 99%
“…In addition to functional changes, organism changes in the brain have been observed in patients with IBDs. Wang et al found that UC participants showed enhanced cortical stability in the medial prefrontal cortex (mPFC), which correlated with severe depression and anxietyrelated measures (39). Bernstein et al cortically mapped visceral pain in patients with gastrointestinal disorders by functional MRI and identified specific areas of activation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. found that UC participants showed enhanced cortical stability in the medial prefrontal cortex (mPFC), which correlated with severe depression and anxiety-related measures ( 39 ). Bernstein et al.…”
Section: Discussionmentioning
confidence: 99%
“…64 Similar increases in connectivity between the dorsal attention network and the somatomotor and occipital/visual network have been reported in irritable bowel syndrome and ulcerative colitis. 94 Functional alterations in the occipital network have also been reported in patients with chronic inflammation and those with chronic pain symptoms, including migraine, chronic low back pain, and fibromyalgia. 53,63,82,94 These alterations involving the occipital network are believed to reflect compromised central processing and modulation of nonpainful multisensory signals and may be a shared central mechanism across chronic pain disorders.…”
Section: Greater Engagement Of Cognitive Control Network In Secondary...mentioning
confidence: 99%